2011
DOI: 10.1186/1471-2377-11-124
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating integrated headache care: a one-year follow-up observational study in patients treated at the Essen headache centre

Abstract: BackgroundOutpatient integrated headache care was established in 2005 at the Essen Headache Centre in Germany. This paper reports outcome data for this approach.MethodsPatients were seen by a neurologist for headache diagnosis and recommendation for drug treatment. Depending on clinical needs, patients were seen by a psychologist and/or physical therapist. A 5-day headache-specific multidisciplinary treatment programme (MTP) was provided for patients with frequent or chronic migraine, tension type headache (TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 18 publications
2
40
0
6
Order By: Relevance
“…The patients included in these studies are qualified as ''difficult-to-treat'' and most of them are migraineurs, but not all of them fulfil the criteria for CM. Overall there is a decrease in headache frequency and headache-related disability in all studies [54,[118][119][120]. The 50 % responder rate after a follow-up of 12 months varies between 36.4 % in the largest survey of 841 patients [54] to 62.7 % in the study by Wallasch et al [118] of 201 patients.…”
Section: Integrated Headache Carementioning
confidence: 83%
See 2 more Smart Citations
“…The patients included in these studies are qualified as ''difficult-to-treat'' and most of them are migraineurs, but not all of them fulfil the criteria for CM. Overall there is a decrease in headache frequency and headache-related disability in all studies [54,[118][119][120]. The 50 % responder rate after a follow-up of 12 months varies between 36.4 % in the largest survey of 841 patients [54] to 62.7 % in the study by Wallasch et al [118] of 201 patients.…”
Section: Integrated Headache Carementioning
confidence: 83%
“…Overall there is a decrease in headache frequency and headache-related disability in all studies [54,[118][119][120]. The 50 % responder rate after a follow-up of 12 months varies between 36.4 % in the largest survey of 841 patients [54] to 62.7 % in the study by Wallasch et al [118] of 201 patients. Interestingly, in the Gaul et al report [120], adherence varied between treatment modalities: 35 % for drug treatment, 61 % for relaxation and 72 % for aerobic exercise.…”
Section: Integrated Headache Carementioning
confidence: 83%
See 1 more Smart Citation
“…Neben dem Kieler Modell, das auf eine stationäre Zuweisung von schwer betroffenen Patienten durch spezialisierte ambulante Versorgungszentren zu einer einzigen Klinik beruht, gibt es das Essener Modell, das eher auf eine regionale Versorgung über die Zusammenarbeit mit primären Versorgern und einem tertiären Versorgungszentrum setzt. In dieser Struktur werden entsprechend betroffene Patienten durch Fachpraxen ambulant in einem Versorgungszentrum vorgestellt, dort wird ein multimodales Assessment unter Einschluss medizinischer, psychologischer und physiotherapeutischer Gesichtspunkte durchgeführt und ein individueller Therapieplan erstellt, der dann in Zusammenarbeit mit dem primär versorgenden Arzt umgesetzt wird [14,44].…”
Section: Integrierte Versorgungsstrukturenunclassified
“…Multidisciplinary approaches have been trialled and discussed in a range of health care settings, including maternity and child health services (Schmied, Mills et al 2010), chronic headache care (Gaul, Bromstrup et al 2011), community-dwelling elders (Vedel, De Stampa et al 2009), eczema sufferers (van Gils, van der Valk et al 2009) and has been found to optimise patient outcomes in palliative care for lung cancer (Borneman, Koczywas et al 2008) and short bowel syndrome (Modi, Langer et al 2008). The dynamics of multidisciplinary teams have been studied in post-cancer follow-up care (Leib, Cieza et al 2011) and maternity care (McIntyre, Francis et al 2011), as well as in a hospital setting (Hogan, Barry et al 2011).…”
Section: Innovations In the Treatment Of Multimorbidity And Implicatimentioning
confidence: 99%